Effectiveness of Cognitive Behavioural Therapy and Eye Movement Desensitization and Reprocessing among Iranian children with post traumatic stress disorder after 2008 Qeshm earthquake - Namazi, Sholeh (2012)
The American Psychiatric Association (2008) has stated that EMDR (eye movement desensitization and reprocessing) may be useful for people who have trouble talking about the traumatic events they have experienced. Although this may be useful for children, the clinical use of EMDR in the treatment of PTSD symptoms in children has not been evaluated. The general objective of this experimental study with randomized pre-test post-test control group design was to compare the effectiveness of EMDR with CBT, a validated intervention in reducing PTSD symptoms among Iranian children 20 months following the 2008 Qeshm earthquake. Six alternative hypotheses were tested. Respondents were 26 elementary school students aged 7 to 12 years old who were diagnosed with PTSD due to the earthquake by a psychiatrist. Respondents were randomly assigned into three groups as follows: nine in the CBT, nine in the EMDR and 8 in the Wait-list Control group. PTSD symptoms severity was evaluated using the UCLA-PTSD DSM-IV Index (Child Form) that had already been modified for use in Iran. Other instruments used included Negative Perception of Earthquake, Relationship to Therapist, Subjective Unit of Distress and Validity of Cognition. Variuos efforts were made to control for internal and external threats of validity. A one-way analysis of covariance (ANCOVA) showed that after participating in 8-12 sessions of psychotherapy, respondents in the CBT and EMDR groups exhibited significant reduction in overall PTSD symptoms compared to the Control group between pre-test to posttest F(2,22)=19.62 p=0.001 (Sig.p<.05). Although the effect of CBT in reducing PTSD symptoms was more than EMDR, the difference was not significant p=.06 (Sig.p>.05). Oneway ANCOVA also showed that there were significant differences in PTSD severity among EMDR, CBT and Control groups between pre-test and post- test by three different PTSD criteria, namely: intrusion F(2,22)=.86, p=.001(Sig.p<.05), avoidance F (2,22)=8.09 (Sig.p<0.5) and arousal (2,22)=.001 (Sig.p<.05). Comparisons between CBT and EMDR groups showed that CBT was significantly more effective in reducing PTSD symptoms in the intrusion (p=.03, Sig.p<.05) and arousal clusters (p=.009, Sig.p<.05) but not in the avoidance cluster (p=.035, Sig.p>.05). Although significant reduction in PTSD symptoms was reported across treatment groups, none of the children were PTSD symptoms-free as measured by the UCLA-PTSD DSM-IV Index at posttest. The results also showed that there were no significant differences in respondents satisfaction between CBT and EMDR, t(16) =.56, p= .57 (sig. p>.05). Delayed post-test showed that posttreatment therapeutic outcomes were maintained during 45 days follow-up in terms of differences between groups F (2, 22) =17.78, p=.02 (Sig. p<.05), but the effects of EMDR improved within this period and differences between CBT and EMDR measures in posttreatment decreased in the Follow-up evaluation, p=.14 (Sig. p<.05).This study showed that both CBT and EMDR were effective in the treatment of PTSD among children. Further studies need to be conducted to determine the usefulness of the EMDR approach for other childhood psychopathologies.